Produksi Jamur Merang (Volvariella volvacea (Bull. ex. Fr) Sing). pada Dua Jenis Limbah Kapas: Production of Straw Mushrooms (Volvariella volvacea (Bull. ex. Fr) Sing). on Two Types of Cotton Wastes - Sudirman, Lisdar Idwan; Rosita, Iros; Dharmaputra, Okky Setyawati (Departemen Biologi, Institut Pertanian Bogor, 2024)
One of the substrates for the growth of straw mushrooms is cotton waste. Based on the cellulose content, trash cotton and dust cotton were selected as substrates. This research was conducted twice at the dry season. The 3,000 g production substrates were a mixture of trash cotton and straw in a ratio of 2:1 (T2J1) and 1:1 (T1J1), dust cotton and straw in a ratio of 2:1 (D2J1) and 1:1 (D1J1). Previously, cotton and straw with the addition of 8% rice bran and 3% lime were composted separately, then mixed, pasteurized and inoculated with 2.5% of spawn. The D2J1 substrate produced higher number and bigger of fruit bodies, with the biological efficiency (BE) of 21.22 and 23.03% for the first and the second experiments, while the BE of T1J1 were only 16.76% and 5.84% and those of D1J1 were 15.63% and 12.45%, those of T2J1 were 16.76% and 0.22% for the first and second experiment respectively. The lowest BE value in these experiments due to incomplete vegetative phase, along with the contamination of Trichoderma sp. In conclusion, the production of straw mushroom fruiting bodies depends on the type of cotton and its ratio to straw.